2007
DOI: 10.1002/nag.659
|View full text |Cite
|
Sign up to set email alerts
|

A non‐coaxial constitutive model for sand deformation under rotation of principal stress axes

Abstract: SUMMARYA constitutive model for the simulation of non-coaxiality, an aspect of anisotropic behavior of sand subjected to the rotation of the principal stress axes, is presented in this paper. Experimental studies have shown that non-coaxiality or non-coincidence of principal plastic strain increments with principal stress axes under loadings involving the rotation of principal stress axes may be considerable. Besides, the rotation of the principal stress axes results in dramatic effects on stiffness and dilata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Based on laboratory observations, a number of advanced constitutive models have been developed, e.g., bounding surface hypoplasticity model (Li and Dafalias 2004;Lashkari and Latifi 2008;Yang and Yu 2012), yield vertex model (Tsutsumi and Hashiguchi 2005), double shearing model (Zhu 2006 a, b), yield vertex and double shearing model (Yu 2008). A state parameter has been introduced in the models to quantify the effect of material anisotropy, and often for simplicity, it is assumed that material anisotropy remains unchanged during the process of loading even though induced anisotropy has been noticed as early as in 1940Õs (Casagrande and Carrillo 1944).…”
Section: ! Introductionmentioning
confidence: 99%
“…Based on laboratory observations, a number of advanced constitutive models have been developed, e.g., bounding surface hypoplasticity model (Li and Dafalias 2004;Lashkari and Latifi 2008;Yang and Yu 2012), yield vertex model (Tsutsumi and Hashiguchi 2005), double shearing model (Zhu 2006 a, b), yield vertex and double shearing model (Yu 2008). A state parameter has been introduced in the models to quantify the effect of material anisotropy, and often for simplicity, it is assumed that material anisotropy remains unchanged during the process of loading even though induced anisotropy has been noticed as early as in 1940Õs (Casagrande and Carrillo 1944).…”
Section: ! Introductionmentioning
confidence: 99%
“…Initial (i.e., inherent) anisotropy can influence the stress-strain behavior, dilatancy, and direction of principal strain rates when granular media are subjected to rotation of principal stress axes (e.g., [24,45,49,54,100]). In the current form, the proposed model only takes into account the effects of stress-induced anisotropy on the sands behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Of the most notable is the vertex-structure (tangential) plasticity model proposed by Rudnicki and Rice [7]. Compared with other non-coaxial theories, such as kinematic hardening boundary surface model [11,12] or subloading surface model [13], the vertex plasticity model was developed in the context of standard elaso-plastic theory. Hence, this class of models can facilitate their use in numerical analysis.…”
Section: Non-coaxial Modelmentioning
confidence: 99%
“…It was also shown that non-coaxiality has great effects on stress dilatancy and cause less dissipation energy [9,10]. As the rotation of principal stress axes, non-coaxiality also has a significant influence on the feature of stress-strain and tends to cause larger unrecoverable strain by softening shear modulus [11][12][13]. More recently, spectral analysis by Qian et al [14] related non-coaxiality to two distinct mechanisms, i.e., anisotropy of material and non-proportionality of loading.…”
Section: Introductionmentioning
confidence: 96%